Help Desk System - Izzat Hafifi, Ahmad Ariza (2012)
Essentially, the Help Desk is a central point which problem or issues are reported and subsequently managed or coordinated. The role of the Help Desk System is providing support for employees within an organization, where the system can give solution the problem are reported as soon as possible. Help Desk System was developed to provide technical information to users and solves technical problem by providing support and information. This system was developed based on observations of current mobile technology growing. With web based and web mobile Help Desk System, organization can access information at anytime and anywhere. In order to finish this project, System Development Life Cycle (SDLC) method has been adopted in developing this project. System Development Life Cycle (SDLC) has been chosen because the system had to be developed in short period of time. Help Desk System has been developed by using Aptana Studio for the interface and PHP (Hypertext Preprocessors) for scripting language and Adobe Dreamweaver 5.5 and mobile jquery for developed the web mobile section.